Kinerja Badan Pengawasan Keuangan dan Pembangunan (BPKP) di Provinsi Sulawesi Utara - Siagian, Mery Krismas; Pangkey, Masje; Rares, Joyce (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: Finance and Development Superfisory Agency is a non – departmental institution formed onlyby Presidential decree.Where many people judge needs to be done over the dissolution of theFinance andDevelopment Superfisory Agency,the reason is because it is necessary for both power and efficiency ofpublic spending because it has too many institutions existing internal control. This research is done onthe employees of Finance and Development Superfisory Agency in North Sulawesi.Thepuspose of thisstudy was to determine the performance of the Finance adnDevelpoment Supervisory Board role inserving the community. The analytical method used is descriptive method in the from of field that isrequired in this study is derived from the result of interviews,field notes and photos- photos as afield.Then the fields obtained by researchers, it will be the field using an interpretive approarch,whereresearchers interpret the meaning of the field that has been collected by giving attention and record asmany aspects studied at the time.Keywords : Performance:Finance and Development Superfisory Agency